Enzymatic hydrolysis of delignified bagasse polysaccharides - Adsul, Mukund G.; Ghule, J. E.; Shaikh, H.; Singh, R.; Bastawade, Kulbhushan B.; Gokhale, D. V.; Varma, Anjanikumar (Carbohydrate Polymers, 2005)
Sugarcane bagasse, consisting of cellulose, xylan, and lignin, was chemically treated to generate bagasse samples with continuously decreasing content of lignin. These bagasse samples were hydrolyzed by cellulase and xylanase enzymes, produced earlier by Penicillium janthinellum NCIM 1171 in the same bagasse polysaccharides production medium. The hydrolysis was carried out by using different concentrations of the enzymes at two different temperatures, 30 and 50 degrees C, taking hydrolysis of Avicel as control. It was found that while the maximum hydrolysis for Avicel was 70% that of some of the bagasse polysaccharides was as high as 95%. The products of hydrolysis were glucose, xylose, and arabinose, as confirmed by high pressure ion chromatography (HPIC). It is interesting to note that arabinose, which constitutes about 10% of the weight of bagasse xylan, could also be released easily by the enzymes. Also, the initial rates of hydrolysis was found to be much higher for the bagasse polysaccharides, and in some cases about 90% of the hydrolysis occurred within 20 h. Amongst all bagasse samples, the sample with (Kappa no. 1.2, lignin content 0.18%) gave the highest degree of hydrolysis at 50 degrees C. Even the bagasse polysaccharide with Kappa no. 16.8 (lignin content 2.5%) underwent greater extent of hydrolysis than Avicel. Apparently, the delignified bagasse medium appears to be a facile medium for the combined hydrolytic action of the cellulase and xylanase enzymes. Considering that sugarcane bagasse is a waste biomass material available in abundance annually, this methodology can be used to value-add to this biomass to produce sugars, which can be fermented to produce biofuels like ethanol. (C) 2005 Elsevier Ltd. All rights reserved.
Keywords: bagasse polysaccharides; Cellulase; chemical treatment; Enzymatic hydrolysis; Penicillium janthinellum; Sugarcane bagasse; Xylanase

Lactic acid production from waste sugarcane bagasse derived cellulose - Adsul, Mukund G.; Varma, Anjanikumar; Gokhale, Digambar V. (Green Chemistry, 2007)
Production of L(+) lactic acid from sugarcane bagasse cellulose, one of the abundant biomass materials available in India, was studied. The bagasse was chemically treated to obtain a purified bagasse cellulose sample, which is much more amenable to cellulase enzyme attack than bagasse itself. This sample, at high concentration (10%), was hydrolyzed by cellulase enzyme preparations (10 FPU g(-1) cellulose) derived from mutants generated in our own laboratory. We obtained maximum hydrolysis (72%), yielding glucose and cellobiose as the main end products. Lactic acid was produced from this bagasse cellulose sample by simultaneous saccharification and fermentation (SSF) in a media containing a cellulase enzyme preparation derived from Penicillium janthinellum mutant EU1 and cellobiose utilizing Lactobacillus delbrueckii mutant Uc-3. A maximum lactic acid concentration of 67 g l(-1) was produced from a concentration of 80 g l(-1) of bagasse cellulose, the highest productivity and yield being 0.93 g l(-1) h(-1) and 0.83 g g(-1), respectively. The mutant Uc-3 was found to utilize high concentrations of cellobiose (50 g l(-1)) and convert it into lactic acid in a homo-fermentative way. Considering that bagasse is a waste material available in abundance, we propose to valorize this biomass to produce cellulose and then sugars, which can be fermented to products such as ethanol and lactic acid.

Strain improvement of penicillium janthinellum ncim 1171 for increased cellulase production - Adsul, Mukund G.; Bastawade, Kulbhushan B.; Varma, Anjanikumar; Gokhale, D. V. (Bioresource Technology, 2007)
The strain of Penicilhuinjanthinellunt NOM 1171 was subjected to mutation involving treatment of Ethyl Methyl Sulfonate (EMS) for 24 h followed by UV-irradiation for 3 min. Successive mutants showed enhanced cellulase production (EMS-UV-8), clearance zone on Avicel containing plate (SM2) and rapid growth on Walseth cellulose agar plates containing 0.2% 2-deoxy-D-glucose (SM3). These mutants were transferred to Walseth cellulose plates containing higher concentration (1.5%) of 2-deoxy-D-glucose (SM4) in which only five mutants showed clearance zone on SM4. All these mutants showed approximately two-fold increase in activity of both FPase and CMCase in shake flask culture when grown on basal medium containing CP-123 (1%) and wheat bran (2.5%). The enzyme preparations from these mutants were used to hydrolyze Avicel. Higher hydrolysis yields of Avicel were obtained with enzyme preparations of EU1. This is the first report on the isolation and selection of mutants based on hydrolysis of Avicel, which is the most crystalline substrate. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: 2-deoxy-D-glucose resistant mutants; cellulase activity; EMS and ultraviolet mutation; Penicillium janthinellum

Utilization of molasses sugar for lactic acid production by lactobacillus delbrueckii subsp delbrueckii mutant Uc-3 in batch fermentation - Dumbrepatil, Arti; Adsul, Mukund G.; Chaudhari, Shivani; Khire, Jayant Malhar; Gokhale, Digambar V. (Applied and Environmental Microbiology, 2008)
Efficient lactic acid production from cane sugar molasses by Lactobacillus delbrueckii mutant Uc-3 in batch fermentation process is demonstrated. Lactic acid fermentation using molasses was not significantly affected by yeast extract concentrations. The final lactic acid concentration increased with increases of molasses sugar concentrations up to 190 g/liter. The maximum lactic acid concentration of 166 g/liter was obtained at a molasses sugar concentration of 190 g/liter with a productivity of 4.15 g/liter/h. Such a high concentration of lactic acid with high productivity from molasses has not been reported previously, and hence mutant Uc-3 could be a potential candidate for economical production of lactic acid from molasses at a commercial scale.

Biochemical characterization of two xylanases from yeast Pseudozyma hubeiensis producing only xylooligosaccharides - Adsul, Mukund G.; Bastawade, Kulbhushan B.; Gokhale, Digambar V. (Bioresource Technology, 2009)
Two distinct xylanases from Pseudozyma hubeiensis NCIM 3574 were purified to homogeneity. The molecular masses of two native xylanases were 33.3 kDa (PhX33) and 20.1 kDa (PhX20). PhX33 is predominant with alpha-helix and PhX20 contained predominantly beta-sheets. Xylanase, PhX33, possesses three tryptophan and one carboxyl residues at the active site. The active site of PhX20 comprises one residue each of tryptophan, carboxyl and histidine. Carboxyl residue is mainly involved in catalysis and tryptophane residues are solely involved in substrate binding. Histidine residue present at the active site of PhX20 appeared to have a role in substrate binding. Both the xylanases produced only xylooligosaccharides (XOS) with degree of polymerization (DP) 3-7 without formation of xylose and xylobiose. These XOS could be used in functional foods or as prebiotics. Lc ms-ms ion search of cryptic digestion of these xylanases revealed that there is no significant homology of peptides with known fungal xylanase sequences which indicate that these xylanases appear to be new. (c) 2009 Elsevier Ltd. All rights reserved.
Keywords: Cellulase-free xylanase; Pseudozyma hubeiensis; Xylooligosaccharides

Cellulases from penicillium janthinellum mutants: solid-state production and their stability in ionic liquids - Adsul, Mukund G.; Terwadkar, Asawari P.; Varma, Anjanikumar; Gokhale, Digambar V. (Bioresources, 2009)
The cellulase production by P. janthinellum mutants on lignocellulosic material such as cellulose or steam exploded bagasse (SEB) in combination with wheat bran was studied in solid state fermentation (SSF). One of the mutants, EU2D21, produced the highest levels of endoglucanase (3710 IU g(-1) carbon source) and beta-glucosidase (155 IU g(-1) carbon source). Ionic liquids are so-called green solvents that have become attractive for biocatalysis. Stability of mutant cellulases was tested in 10-50% of the ionic liquid 1-butyl-3-methylimidazolium chloride ([bmim]Cl). FPA and CMCase were significantly stable in 10% ionic liquid after 5h. beta-glucosidase showed 85% of its original activity after 5 h incubation in 30% ionic liquid and retained 55% of its activity after 24 h. This enzyme preparation hydrolyzed ionic-liquid-treated SEB completely in 15 h in the presence of 20% ionic liquid. These studies revealed that there is no need of regenerating cellulose after ionic liquid treatment, since cellulase of mutant strain was found to be significantly stable in the ionic liquid.
Keywords: Cellulase stability; Ionic liquid; Mutant cellulase; Solid state fermentation

D-(-)-Lactic acid production from cellobiose and cellulose by Lactobacillus lactis mutant RM2-24 - Singhvi, Mamta; Joshi, Dipti; Adsul, Mukund G.; Varma, Anjanikumar; Gokhale, Digambar V. (Green Chemistry, 2010)
Lactobacillus lactis mutant RM2-24 utilizes cellobiose efficiently, converting it into D-(-)-lactic acid. Cellobiose-degrading enzyme activities were determined for whole cells, cell extracts and disrupted cells. Aryl-beta-glucosidase activity was detected in whole cells and disrupted cells, suggesting that these activities are confined to the cells. The mutant produced 80 g l(-1) of lactic acid from 100 g l(-1) of cellobiose with 1.66 g l(-1) h(-1) productivity. Production of D-lactic acid from different cellulose samples was also studied. The cellulose samples at high concentration (10%) were hydrolyzed by cellulase enzyme preparation (10 FPU g(-1) cellulose) derived from Penicillium janthinellum mutant EU1 generated in our own laboratory. We obtained a maximum 72% hydrolysis, yielding glucose and cellobiose as the main end products. Lactic acid was produced from these cellulose samples by simultaneous sacchari. cation and fermentation (SSF) in a media containing a cellulase enzyme preparation derived from Penicillium janthinellum mutant EU1 and cellobiose utilizing Lactobacillus lactis mutant RM2-24. A maximum lactic acid concentration of 73 g l(-1) was produced from a concentration of 100 g l(-1) of bagasse-derived cellulose, the highest productivity and yield being 1.52 g l(-1) h(-1) and 0.73 g g(-1), respectively. Considering that bagasse is a waste material available in abundance, we propose to use this biomass to produce cellulose and then sugars, which can be fermented to valuable products such as ethanol and lactic acid.

Combined strategy for the dispersion/dissolution of single walled carbon nanotubes and cellulose in water - Adsul, Mukund G.; Rey, Diego A.; Gokhale, Digambar V. (Journal of Materials Chemistry, 2011)
Co-dispersion of native cellulose and single walled carbon nanotubes in water is demonstrated. The pH of the water should be between 6 and 10 for better dispersion. Raman spectra confirm debundling of nanotubes in water and FTIR spectra reveal that the co-solubility is likely caused through disruption of intramolecular hydrogen bonds in the cellulose by hydroxyl groups present on nanotubes surface and the creation of intermolecular hydrogen bonds between cellulose and carbon nanotubes. This is a very simple method for co-dispersion/dissolution of nanotubes and cellulose in water without covalent modifications and expands the repertoire of nanotube modification strategies that are amenable to biological applications.

Comparative production of cellulases by mutants of penicillium janthinellum NCIM 1171 and its application in hydrolysis of avicel and cellulose - Singhvi, M. S.; Adsul, Mukund G.; Gokhale, D. V. (Bioresource Technology, 2011)
Mutants of Penicillium janthinellum NCIM 1171 were evaluated for cellulase production using both submerged fermentation (SmF) and solid state fermentation (SSF). Mutant EU2D-21 gave highest yields of cellulases in both SmF and SSF. Hydrolysis of Avicel and cellulose were compared using SmF and SSF derived enzyme preparations obtained from EU2D-21. Surprisingly, the use of SSF derived preparation gave less hydrolysis compared to SmF derived enzymes. This may be due to inactivation of beta-glucosidase at 50 degrees C in SSF derived enzyme preparations. SmF derived enzyme preparations contained both thermostable and thermosensitive beta-glucosidases where as SSF derived enzyme preparations contained predominantly thermosensitive beta-glucosidase. This is the first report on less thermostability of SSF derived p-glucosidase which is the main reason for getting less hydrolysis. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: beta-Glucosidase thermostability; Mutant EU2D-21; Solid state fermentation; Submerged fermentation

Development of biocatalysts for production of commodity chemicals from lignocellulosic biomass - Adsul, Mukund G.; Singhvi, M. S.; Gaikaiwari, Shalaka A.; Gokhale, D. V. (Bioresource Technology, 2011)
Lignocellulosic biomass is recognized as potential sustainable source for production of power, biofuels and variety of commodity chemicals which would potentially add economic value to biomass. Recalcitrance nature of biomass is largely responsible for the high cost of its conversion. Therefore, it is necessary to introduce some cost effective pretreatment processes to make the biomass polysaccharides easily amenable to enzymatic attack to release mixed fermentable sugars. Advancement in systemic biology can provide new tools for the development of such biocatalysts for sustainable production of commodity chemicals from biomass. Integration of functional genomics and system biology approaches may generate efficient microbial systems with new metabolic routes for production of commodity chemicals. This paper provides an overview of the challenges that are faced by the processes converting lignocellulosic biomass to commodity chemicals. The critical factors involved in engineering new microbial biocatalysts are also discussed with more emphasis on commodity chemicals. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Biomass utilization; Commodity chemicals; Ethanol; Lactic acid; Microbial cellulases

Differential induction, purification and characterization of cold active lipase from Yarrowia lipolytica NCIM 3639 - Yadav, K. N. Sathish; Adsul, Mukund G.; Bastawade, Kulbhushan B.; Jadhav, D. D.; Thulasiram, H. V.; Gokhale, D. V. (Bioresource Technology, 2011)
The production, purification and characterization of cold active lipases by Yarrowia lipolytica NCIM 3639 is described. The study presents a new finding of production of cell bound and extracellular lipase activities depending upon the substrate used for growth. The strain produced cell bound and extracellular lipase activity when grown on olive oil and Tween 80, respectively. The organism grew profusely at 20 degrees C and at initial pH of 5.5, producing maximum extracellular lipase. The purified lipase has a molecular mass of 400 kDa having 20 subunits forming a multimeric native protein. Further the enzyme displayed an optimum pH of 5.0 and optimum temperature of 25 degrees C. Peptide mass finger printing reveled that some peptides showed homologues sequence (42%) to Yarrowia lipolytica LIP8p. The studies on hydrolysis of racemic lavandulyl acetate revealed that extracellular and cell bound lipases show preference over the opposite antipodes of irregular monoterpene, lavandulyl acetate. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Cell bound lipase; Cold active lipase; Extracellular lipase; Lavandulyl acetate; Oligomeric lipase

Enhanced enzymatic hydrolysis of cellulose by partial modification of its chemical structure - Shaikh, H. M.; Adsul, Mukund G.; Gokhale, D. V.; Varma, Anjanikumar (Carbohydrate Polymers, 2011)
A series of 2,3-dialdehyde celluloses with different degrees of oxidation were used for deriving corresponding dicarboxylate, dicarboxy, and Schiff's base cellulose derivatives. The dialdehyde cellulose was hydrolyzed by cellulase to a lower extent than the starting cellulose, except at high levels of aldehyde content (above 50%). For dicarboxylate and dicarboxy celluloses, the highest level of oxidized NaDCC and DCC hydrolysed up to 70 and 60% respectively which was 3-4 times more than cellulose. The 2,3-dioxime cellulose derivative hydrolyzes only up to 16.3% for the highest level of oxidized dioxime. In the case of 2,3-diethylimine cellulose, all derivatives hydrolyse faster than the native cellulose. Up to 75% hydrolysis was observed for 2,3-diethyimine cellulose-50, 2,3-dipropylimine and 2,3-dibutylimine cellulose. The 2,3-dibenzylimine cellulose hydrolyses a little slower than the alkylimine derivatives. The 2,3-dihydrazone cellulose derivatives with all level of oxidation showed resistance towards enzymatic hydrolysis. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: 2; 3-Dialdehyde celluloses; 3-Dibenzylimine cellulose; 3-Dibutylimine cellulose; 3-Dicarboxy celluloses; 3-Diethyimine cellulose; 3-Dihydrazone cellulose; 3-Dipropylimine cellulose; Cellulase; Enzymatic hydrolysis